Local summer insolation and greenhouse gas forcing drove warming and glacier retreat in New Zealand during the Holocene. (15th August 2021) - Dowling, Lisa; Eaves, Shaun; Norton, Kevin; Mackintosh, Andrew; Anderson, Brian; Hidy, Alan; Lorrey, Andrew; Vargo, Lauren; Ryan, Matthew; Tims, Stephen
Abstract: Geological climate archives from the Holocene Epoch provide baseline information concerning natural climate variability. Temperate mountain glacier extent is sensitive to summer air temperature, thus geological records of past glacier length changes are a useful proxy for this climatic variable. Here we present a new cosmogenic 10 Be chronology of glacier length changes at Dart Glacier in the Southern Alps, New Zealand. Prominent moraines deposited 321 ± 44 yr ago (n = 11) and 7.8 ± 0.3 ka (n = 5) show glaciers during the Little Ice Age were less extensive than during the early Holocene. This pattern of net Holocene glacier retreat is consistent with emerging data from other catchments in New Zealand and across the southern mid-latitudes. Using the physical framework of a transient global climate model simulation, we suggest that cool summers in the early Holocene were promoted by the local summer insolation minimum, together with low atmospheric greenhouse gas concentrations, causing an early Holocene austral glacial maximum. An insolation-driven reduction in seasonality at southern mid-latitudes may reconcile differences between early Holocene temperature reconstructions where climate proxies have different seasonal sensitivities. We suggest that rising greenhouse gas concentrations after 7 ka caused regional-scale glacier retreat and appear to be the dominant driver of multi-millennial summer temperature trends in the southern mid-latitudes during the present interglacial. Highlights: New 10 Be moraine chronology connects prehistoric and modern glacier observations. Net retreat of New Zealand glaciers during the Holocene. Insolation and greenhouse gases most likely drivers of regional Holocene climate.